Realizing high capacitance and rate capability in polyaniline by enhancing the electrochemical surface area through induction of superhydrophilicity - Soni, Roby; Kashyap, Varchaswal; Nagaraju, Divya; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2018)
Polyaniline (PANI) as a pseudocapacitive material has very high theoretical capacitance of 2000 F g(-1). However, its practical capacitance has been limited by low electrochemical surface area (ESA) and unfavorable wettability toward aqueous electrolytes. This work deals with a strategy wherein the high ESA of PANI has been achieved by the induction of superhydrophilicity together with the alignment of PANI exclusively on the surface of carbon fibers as a thin layer to form a hybrid assembly. Superhydrophilicity is induced by electrochemical functionalization of the Toray carbon paper, which further induces superhydrophilicity to the electrodeposited PANI layer on the paper, thereby ensuring a high electrode-electrolyte interface. The Toray paper is electrochemically functionalized by the anodization method, which generates a highly active electrochemical surface as well as greater wettability (superhydrophilic) of the carbon fibers. Because of the strong interaction of anilinium chloride with the hydrophilic carbon surface, PANI is polymerized exclusively over the surface of the fibers without any appreciable aggregation or agglomeration of the polymer. The PANI-Toray paper assembly in the solid-state prototype supercapacitor can provide a high gravimetric capacitance of 1335 F g(-1) as well as a high areal capacitance of 1.3 F cm(-2) at a current density of 10 A g(-1). The device also exhibits high rate capability, delivering 1217 F g(-1) at a current density of 50 A g(-1) and a high energy density of 30 W h kg(-1) at a power density of 2 kW kg(-1).
Keywords: electrochemical active sulfate area; electrochemical functionalization; electropolymerization; polyaniline; supercapacitor; superhydrophilic